ANALYSIS OF SUPPORTING CAPACITY OF INTEGRATED ANTENATAL SERVICES IN TLOGOSARI WETAN PUSKESMAS, SEMARANG CITY - Silvia Calista; Retno Sunu Astuti; Yuliana Kristanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
One indicator of the success of development in the health sector is the decline in maternal mortality. The problem of the quality of health in mothers can be overcome by the existence of Integrated Antenatal Services. In line with the Minister of Health Regulation No. 97 of 2014 that all pregnant women must receive integrated, comprehensive and quality antenatal care. In its implementation, for the last five years at the Tlogosari Wetan Health Center, there are still findings of death in pregnant women. This condition indicates that the integrated antenatal care has not been carried out optimally by the Tlogosari Wetan Health Center. Successful implementation requires the carrying capacity of the resources needed to achieve the success of a program, otherwise it will be an obstacle if the availability is not optimal. The aims of this study were to: (1) analyze the implementation of integrated antenatal care at the Tlogosari Wetan Health Center and (2) analyze the obstacles to the carrying capacity of integrated antenatal services at the Tlogosari Wetan Health Center. This study uses a qualitative descriptive approach and uses the Shabeer Cheema Implementation Theory with a focus on carrying capacity. The research technique used purposive The results of this study indicate that the implementation of integrated antenatal care at the Tlogosari Wetan Health Center has not been optimal. The inhibiting factors for integrated antenatal support are (1) incompatibility of services in accordance with SOPs, (2) lack of health resources for midwives and the quality of training that is not evenly distributed, (3) integrated antenatal funding that is not optimal, and (4) medical equipment Inadequate ultrasound equipment in antenatal care. Several efforts are needed, such as reviewing the implementation SOP, equitable distribution and integrated antenatal training, improving financial management, procurement of health equipment and improvement of puskesmas infrastructure.